Testing how antagonistic interactions impact the robustness of plant-pollinator networks - Briggs, Heather; Ayers, Carolyn A.; Armsworth, Paul R.; Brosi, Berry J. (Journal of Pollination Ecology, 2019)
Given ongoing pollinator declines, it is important to understand the dynamics of linked extinctions of plants driven by pollinator extinctions. Topological robustness models focused on this question suggest relatively high robustness of plant species to pollinator species extinctions. Still, existing robustness models typically assume that all interactions in plant-pollinator networks are positive, which is clearly not always the case. For example, many pollinators remove floral resources without transferring pollen, or even damage floral structures in the case of nectar robbing. Here we introduce antagonistic interactions into plant-pollinator networks and assess the resilience of plant communities to pollinator species losses. Incorporating antagonistic interactions leads to lower network robustness, i.e. an increased rate of plant species loss (as compared to networks with only mutualistic interactions) in empirical plant-pollinator networks. In conjunction with extinction order, the addition of increasingly antagonistic interactions was idiosyncratic in that it did not always magnify the effects of extinction order across the three networks. These results underscore the importance of considering the full spectrum of interaction outcomes when assessing robustness to coextinctions in plant-pollinator networks, as well as other ecological systems.